Parametric Set-Valued Vector Quasi-Equilibrium Problems. (6th April 2010) - Fan, Liya; Li, Aiqin
Abstract : Two kinds of parametric set-valued vector quasi-equilibrium problems are introduced. The existence of solutions to these problems is studied. The upper and lower semicontinuities of their solution maps with respect to the parameters are investigated.